1998
DOI: 10.1098/rspb.1998.0425
|View full text |Cite
|
Sign up to set email alerts
|

On the strategic stability of monitoring: implications for cooperative wildlife programmes in Africa

Abstract: Game-theoretic modelling is used to study the design of an agreement among residents to conserve a wildlife resource, by not hunting animals illegally, when the community monitors its own behaviour. The analysis demonstrates that such an agreement may be very much costlier for a government to sustain if its incentive structure avoids the payment of monitoring fees, and instead relies on community bene¢ts for conservation, with bonuses for reporting poachers. Conditions are identi¢ed for the agreement to be sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 18 publications
0
24
0
Order By: Relevance
“…Previous studies examining the enforcement of resourceuse rules have tended to concentrate on the users' incentives (for example fishers or poachers; Leader-Williams & MilnerGulland 1993;Skonhoft & Solstad 1996;Damania et al 2005). However, the success of enforcement also depends crucially on monitors' incentives to carry out their duties (Mookherjee & Png 1995;Mesterton-Gibbons & Milner-Gulland 1998;Robinson et al 2010). The model presented here explores the effects on conservation outcomes of changes to three potential policy levers intended to promote monitoring and discourage poaching.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies examining the enforcement of resourceuse rules have tended to concentrate on the users' incentives (for example fishers or poachers; Leader-Williams & MilnerGulland 1993;Skonhoft & Solstad 1996;Damania et al 2005). However, the success of enforcement also depends crucially on monitors' incentives to carry out their duties (Mookherjee & Png 1995;Mesterton-Gibbons & Milner-Gulland 1998;Robinson et al 2010). The model presented here explores the effects on conservation outcomes of changes to three potential policy levers intended to promote monitoring and discourage poaching.…”
Section: Discussionmentioning
confidence: 99%
“…Mesterton-Gibbons and Milner-Gulland (1998) found that the payment of fees was essential for the stability of monitoring as a strategy. The discrepancy between this finding and ours results from differences in the range of behaviours which modelled individuals were allowed to adopt.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mesterton-Gibbons and Milner-Gulland (1998) posited that Zimbabwean local communities used cooperative game theory to determine the conditions under which community self-monitoring would ensure conservation occurs. These researchers in Zimbabwe concluded that ""no self-monitoring agreement can be sustainable without a payment to each individual that exceeds the opportunity cost of monitoring even if no one is poaching"".…”
Section: Common Property Regimesmentioning
confidence: 99%
“…Whilst economic models (e.g. Mesterton-Gibbons & Milner-Gulland 1998) and institutional analysis (e.g. Agrawal & Gibson 1999) provide insights into decision-making of individuals, social psychological variables also influence decision-making and behaviour (Salafsky et al 2001;Horwich & Lyon 2007;St John et al 2011).…”
Section: Addressing Human Threatsmentioning
confidence: 99%